Cash Transfer Program in Olilan Village, Walea Islands Sub-District, Tojo Una-Una District - Mahadi, Rusli (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The purpose of this study was to determine the Direct Cash Assistance Program (BLT) in Olilan Village, Walea Islands Sub-district, Tojo Una-Una Regency. The research method used is a qualitative method, which is a method that analyzes and interprets words and interview results with the aim of finding the meaning of a phenomenon. The data collection techniques used were observation, interview and documentation. The data analysis technique used is the Miles and Huberman interactive model. Based on the results of the research, the analysis of the discussion of this study concludes that the direct cash transfer program (BLT) seen from the aspects of socialization, data, delay in disbursement, assistance has not been optimally carried out in Olilan Village, Walea Islands Sub-district, Tojo Una-una Regency. From the socialization aspect, this program has not been effective because the village apparatus still lacks socialization and synchronization in the implementation of the Direct Cash Assistance Program (BLT). From the data aspect, this program was also not effective because the existing data did not accommodate the poor who really needed BLT. In addition, from the aspect of delayed disbursement, this program has not run well because the disbursement of assistance through BLT is often not on time. The schedule for the distribution of assistance that had been determined through a joint meeting between the village government and the beneficiary community was often not in accordance with the plan or time that had been determined.